Analysis of influencing factors of corneal edema after phacoemulsification for diabetic cataract: Influencing factors of corneal edema for diabetic cataract - Jing, Zhifu; Hao, Junhua; Sun, Lijuan; Zhao, Xiaoli; Jia, Xinliang; Liu, Zhiqiang; Zhang, Kun (Cellular and Molecular Biology, 2023)
The paper aimed to explore the influence factors of corneal edema after phacoemulsification for diabetic cataracts. For this aim, 80 patients (80 eyes) with senile cataracts who underwent phacoemulsification implantation in our hospital from August 2021 to January 2022 were included in this study, including 39 males (48.75%) and 41 females (51.25%), with an average age of 70.35±5.22 years. The OCT system during ophthalmology was used to capture corneal OCT images in the center of the cornea in real time before the phacoemulsification (the phacoemulsification probe just entered the anterior chamber after the balanced saline left the separated nucleus), at the end of phacoemulsification (when the phacoemulsification ultrasound probe was still in the anterior chamber and the perfusion pressure did not change compared with that in the previous step), at the end of perfusion aspiration (after the perfusion aspiration probe left the anterior chamber), and after surgery (after the watertight incision is closed). The corneal thickness was measured at each time point using Photoshop software. AL, curvature and ACD were measured using IOL-Master bio-measurement technology, and ACD referred to the distance between the front surface of the cornea and the front surface of the lens. Endothelial cell density was measured using CIM-530 non-contact mirror microscope. A handheld rebound tonometer was used to measure intraocular pressure and optical coherence tomography was used to assess the macular area of the fundus. Fundus photography was performed with a non-diffuse fundus camera. The results indicated that the preoperative corneal thickness was 514.35±29.62 μm, and the average corneal thickness at the end of the operation was 535.26±30.29μm, which was increased by 20.91±1.67 μm compared with that before operation (P<0.05), and the increase rate of corneal thickness was 4.07%. The corneal thickness of patients tended to increase with the increase in operation time and intraocular operation time (P<0.05). The distribution of corneal edema-related features showed that 42.50% of patients had persistent edema at the time of cataract surgery. The median onset time of corneal edema in the remaining patients was 5.44 years (1.96-21.35 years for 90% CR). The higher the nuclear hardness, the more severe the cataract, and the higher APT, EPT, APE, and TST (P<0.05). The older the patient, the higher the grade of cataract nucleus, and the higher EPT, APE, and TST, the greater the intraoperative corneal thickening (P<0.05). The higher the maximum area of endothelial cells, the greater the intraoperative corneal thickness increase, the lower the corneal endothelial cell density and the greater the intraoperative corneal thickness increase (P<0.05). It was concluded that postoperative corneal edema in phacoemulsification surgery for diabetic cataracts is closely related to intraocular perfusion pressure, nuclear hardness of lens, the density of corneal endothelial cells, the energy of phacoemulsification and duration.